Traditional Cemeteries as Open Air Museums. Investigations on the Potential of the General Cemetery of Santiago de Chile - Valencia Palacios, Marco (2023)
This article seeks to recognize the potential of traditional cemeteries as open-air museums. For this purpose, the cultural values present in the cemeteries are defined as follows, specifying the nature of the assets defining the funerary heritage. From a critical point of view the difficulties faced by nineteenth-century cemeteries in the present day are pointed out, indicating the main challenges in terms of preservation and patrimonial valorization. For this purpose, a study of references is carried out by means of documentary and bibliographic sources. Finally, it explores the museum potential of Chilean cemeteries, taking as a specific case the General Cemetery of Santiago de Chile.